Primary hyperparathyroidism and vitamin D deficiency - Gyuzel E. Runova ("Consilium Medicum" Publishing house, 2021)
Primary hyperparathyroidism (PHPT) is the third most common endocrine disease after diabetes mellitus and thyroid pathology. Recent epidemiological and experimental data have shown that long-term maintenance of low vitamin D levels in the blood can lead to the development of hyperplastic processes in the cells of the parathyroid glands, followed by autonomous production of parathyroid hormone. In PHPT vitamin D insufficiency or deficiency according to various sources occurs with a frequency of 5377% of cases. The literature review indicates more severe disease in patients with concomitant vitamin D deficiency. The expediency of preoperative assessment of vitamin D levels in all patients with PHPT in order to minimize the risk of hypocalcemia after parathyroidectomy is discussed. This article presents the relationship between vitamin D deficiency and PHPT, as well as possible methods for correcting vitamin D deficiency in PHPT. Molecular and cellular mechanisms of the occurrence of pathological processes in the parathyroid glands under conditions of low vitamin D levels are presented.